Understanding relationships between posttraumatic stress disorder symptoms, binge-eating symptoms, and obesity-related quality of life: the role of experiential avoidance. Issue 3 (4th May 2021) - Wooldridge, Jennalee S.; Herbert, Matthew S.; Dochat, Cara; Afari, Niloofar
ABSTRACT: Obesity, binge-eating symptoms, and PTSD symptoms commonly co-occur. Avoidance, a key feature of PTSD and proposed mechanism of binge-eating, is one potential mechanism for explaining this clinical overlap. The purpose of the current study was to: 1) examine the associations between PTSD symptoms (PTSD Checklist-Civilian; PCL-C) and measures of bingeeating symptoms (Binge Eating Scale; BES) and obesity-related quality of life (Obesity Related Well-Being Questionnaire-97; ORWELL-97) in a sample of veterans with overweight or obesity ( N = 89), and 2) determine whether experiential avoidance (The Acceptance and Action Questionnaire–II; AAQ-II) explains the relationship between PTSD symptoms and binge-eating symptoms, and PTSD symptoms and obesity-related quality of life, respectively. Scores on the PCL-C, BES, ORWELL-97, and AAQ-II were all significantly correlated. Linear regression analyses indicated that higher PCL-C scores were related to higher scores on the BES and ORWELL-97 after controlling for potentially confounding factors (BMI and race). Effect sizes were in the medium-large range. Further, AAQ-II mediated the relationship between PCL-C and ORWELL-97, but did not mediate the relationship between PCL-C and BES. These findings suggest that experiential avoidance should be considered in interventions addressing co-occurring PTSD, binge-eating, and poor obesity-related well-being. Longitudinal research is needed to better understand directionality of these relationships and changes over time.